D–π–A manufactured organic dye molecules with different spacers for highly efficient reliable DSSCs via computational analysis. Issue 7 (3rd May 2022) - Govindarasu, R.; Subramanian, M. K.; Arunkumar, A.; Anbarasan, P. M.; Shkir, Mohd
ABSTRACT: Based on (E)-2-cyano-3-(5-(2-(4-(dimethylamino)phenyl)ethynyl)thiophene-2-yl)acrylic acid (CSD-01) dye, newly designed isolated organic (CSDS1-CBDS7) molecules were investigated for dye-sensitised solar cells (DSSCs) application using the density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations. The electronic and optimised geometry of the CSDS1–CSDS7 derivatives were contained in the electron-donor (D), π-linker (π) and electron–acceptor (A) groups to form a D–π–A structure. Different hybrid functionals were used to get a maximum value of optical absorption UV-Vis peak in CSD-01 dye. Accordingly, a ωB97XD was sensibly found by calculating the UV-Vis in CSD-01. Further, UV-Vis spectra were used to design newly efficient sensitisers by the TD-DFT-ωB97XD-6-31G(d) theory. The CSDS1–CSDS7 dyes were implemented on the driving force of the electron injection ( Δ G inject ), dye regeneration ( Δ G reg ), dipole moment ( μ normal ), light-harvesting efficiency, theoretical open-circuit photovoltage ( e V OC ), excited-state lifetime ( τ ), the density of state, the exciton binding energy ( E b ) and molecular electrostatic potential. The highest occupied molecular orbitals below the redox electrolyte and lowest unoccupied molecular orbitals above the conduction band edge of the TiO2 surface were successfully identified. Finally, the newly CSDS5 and CSDS6 structured sensitisers were offered theoretical tools for highly efficient organic photosensitisers for further research.